The Effect of Using 3D-Virtual Worlds and Real Worlds on Creative Thinking - Mohamed M. Al-Hileh, Naheda A. Al-Momani, (Opción, 2019)
This study aimed at inquiring the effect of using 3D virtual worlds and real worlds on the creative thinking of basic tenth-grade female students in physics via a quasi-experimental methodology. The findings indicated that there were significant differences at (α ≤ 0.05) between means of students in creative thinking tests, attributed to teaching methods, in favor of the group that studied by using 3D virtual worlds. In conclusion, the effect of 3D Virtual World to renovate pedagogy in learning institutions is impartial and vital for the sustainability of the process.